(untitled) (Research, Society and Development, 2021)
Currently, there is a constant search for new chemical compounds through plant extracts and phytochemical compounds that do not cause so many side effects in the oral cavity and that have good antimicrobial properties. Therefore, the present study evaluated the synergistic antimicrobial efficacy of mouthwashes containing thymol and carvacrol when compared with 0.12% chlorhexidine mouthwash after bilateral lower third molar extraction. Nineteen healthy (male and female) patients (n = 19) aged between 18 and 30 years, of both sexes, treated at the Faculty of Dentistry of Mato Grosso do Sul (UFMS, MS, Brazil) participated in this study. All patients were submitted to two different therapeutic treatments, divided into two groups: group 1 (control) - patient used 0.12% chlorhexidine mouthwash solution; group 2 (experimental) - patient used 0.05% thymol and 0.025% carvacrol solutions. The suture was removed at seven postoperative days and aseptically transferred to a tube containing sterile potassium buffer saline solution. Samples were submitted to microbiological analysis at the Microbiology Laboratory at UFMS. The mean and standard deviation of colony forming units/ml of isolate microorganisms in the suture grown in BHI agar obtained from the control and experimental groups were 4.766 x 106 ± 4.069 and 4.847 x 106 ± 3.971, respectively. In conclusion, the thymol and carvacrol based mouthwash showed antimicrobial effectivity in biofilm adherence of the silk thread after extraction of third molars.